Eksplorasi Beberapa Alternatif Metode Penelitian Daring Untuk Bidang Perencanaan Wilayah dan Kota - Achmad Djunaedi (REKA RUANG, 2021)
Research conducted online has long been practiced and many research methods have been developed for it. But the current pandemic has prompted more research to be done online; also included in the area of ​​urban and regional planning (PWK). This research seeks to assist PWK students in conducting online research, by introducing various online research methods, as well as ways to convert offline research proposals to online research. Because many pieces of research in the field of PWK are related to location, spatial, and physical areas, some of these studies are quite difficult to do online, but there are still many kinds of online data collection methods that can be utilized. However, online research also opens up new opportunities that were previously difficult (when using offline research methods) to do, including analysis of digital documents collected online, as well as a wider geographic coverage because data collection is done online, there is no need to visit locations.